Cutaneous adverse events: a predictor of tumour response under anti‐PD‐1 therapy for metastatic melanoma, a cohort analysis of 189 patients. (27th April 2020) - Bottlaender, L.; Amini‐Adle, M.; Maucort‐Boulch, D.; Robinson, P.; Thomas, L.; Dalle, S.
Abstract: Introduction: Cutaneous adverse events (AEs) are the most prevalent toxicity under checkpoint inhibitors in clinical trials. In 'real‐life' conditions of use, skin toxicities under anti‐PD‐1 have not been described to date in a large cohort. The objective of this study was to determine the clinical features of skin toxicities in patients with advanced melanoma receiving anti‐PD‐1 therapy under 'real‐life' conditions of use. Secondary objectives were to evaluate the characteristics of patients with skin toxicities and to analyse associated extra‐cutaneous toxicities, progression‐free survival (PFS) and overall survival (OS). Patients and methods: Advanced melanoma patients treated with nivolumab or pembrolizumab between August 2014 and October 2017 were included. Patients lost to follow‐up or receiving anti‐PD‐1 as part of a clinical trial were excluded. Results: One hundred and eighty‐nine patients with metastatic melanoma (with 109 men (57.7%) were included. Cutaneous AE occurred in 39 patients (20.6%). The three most prevalent cutaneous AEs were skin eruption (macular–papular or eczematous) ( n = 18, 9.5%), vitiligo ( n = 16; 8.5%) and isolated pruritus ( n = 5, 2.6%). Grade 3–4 skin toxicity was diagnosed in five patients (2.6%). Atopy (28.2% vs. 12.0%; P = 0.024), hypereosinophilia (20.5% vs. 8.7%; P = 0.046), thyroiditis (17.9% vs. 4.7%; P = 0.011) and renal toxicity (15.4% vs. 4%; P = 0.019) were significantly associated with cutaneous AE. Patients with skin eruption (log‐rank = 0.001), vitiligo (log‐rank = 0.001) and any type of cutaneous AE (log‐rank < 0.001) had a better overall survival. Conclusions: Cutaneous AEs are frequent and often manageable toxicity and were a predictor of tumour response in melanoma patients under anti‐PD‐1 therapy in this cohort.